Localisation and the design and production of sustainable products. (23rd September 2008) - Dogan, Cagla; Walker, Stuart
This paper presents an innovative approach to design research that integrates design-based research in its methodology and which explores ways of integrating 'the local' within product design and production in order to more effectively address sustainable principles within our conceptual frameworks of 'material culture' – its design, production and post-use processing. The concept proposed here, termed integrated scales of design and production not only suggests a more environmentally responsible notion of material culture, but one that also enables local cultural preferences and tastes to be explored. It is an approach that recognises the benefits of mass-produced uniformity and the benefits of local and regional diversity.